Factors Influencing Job Satisfaction of the Workers: An Empirical Study on Readymade Garment (Rmg) Sector in Bangladesh (British Journal of Multidisciplinary and Advanced Studies, 2022)
This study aims to indentify the factors of workers job satisfaction of readymade garment sectors in Bangladesh. To explore this objective, sixty five (65) male and female workers of different garments, located in Savar, Ashulia and Gazipur at Dhaka, Bangladesh, were selected by random sampling technique. Data has been collected through structured questionnaire. Actually, in this study, data has tested with 8 distinct variables collected from intensive literature review. The collected data were analyzed by using SPSS software (Version-20) by adopting the statistical techniques, regression analysis. Based on the basic findings, this study showed that out of the 8 factors, three factors i.e. attractive salary, good job security and better working environment have strong influence on workers job satisfaction of readymade garments sector in Bangladesh and rest of the factors i.e. recognition & reward, supervisor behavior, decision making opportunity, communication system and training facilities have moderate influence on workers job satisfaction in RMG sector in Bangladesh.
Keywords: Bangladesh; Job Satisfaction; Readymade Garments